2018
DOI: 10.1176/appi.ps.201700130
|View full text |Cite
|
Sign up to set email alerts
|

Denial of Suicide Attempt Among Hospitalized Survivors of a Self-Inflicted Gunshot Wound

Abstract: Patients' nondisclosure of suicidal intent following a self-inflicted GSW may present a barrier to care for patients whose injuries are the result of a suicide attempt. Implications for reducing barriers to care for a high-risk population are discussed, including the impact of nondisclosure on future treatment and the potential utility of brief interventions for suicide risk reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…17 Furthermore, intentional self-harm firearm injuries are rarely to the upper extremity, especially the upper extremity alone. 18 This led us to believe that many self-inflicted accidental injuries were being coded as “suicide/self-inflicted injury.” We tested this by quantifying the “suicide/self-inflicted injury” and “intentional self-harm” data by year. Between 2007 and 2014, there were over 2000 cases per year coded “suicide/self-inflicted injury.” In 2016 and 2017, there were fewer than 100 cases per year coded “intentional self-harm.” Based on this, we have presented results to identify these coding issues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Furthermore, intentional self-harm firearm injuries are rarely to the upper extremity, especially the upper extremity alone. 18 This led us to believe that many self-inflicted accidental injuries were being coded as “suicide/self-inflicted injury.” We tested this by quantifying the “suicide/self-inflicted injury” and “intentional self-harm” data by year. Between 2007 and 2014, there were over 2000 cases per year coded “suicide/self-inflicted injury.” In 2016 and 2017, there were fewer than 100 cases per year coded “intentional self-harm.” Based on this, we have presented results to identify these coding issues.…”
Section: Methodsmentioning
confidence: 99%
“…17 Furthermore, intentional self-harm firearm injuries are rarely to the upper extremity, especially the upper extremity alone. 18 This led us to believe that many self-inflicted accidental injuries were being coded as "suicide/self-inflicted injury." We tested this by quantifying the "suicide/selfinflicted injury" and "intentional self-harm" data by year.…”
Section: Methodsmentioning
confidence: 99%
“…In a review by Luoma et al, the authors identified that further measures were needed to reach patient populations underrepresented in mental health settings, including young men and those with poor social determinants of health. [15][16][17] To limit access for those who exhibit risk factors for suicidality, numerous states have incorporated "red flag" laws that allow family or law enforcement to confiscate firearms in certain circumstances. A study by Swanson et al 18 determined there was at least a modest deterrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…There are substantially more subtle indicators that the information shared by the client represents only a partial truth or a fabrication. It may be that the client says that they were "only joking" or contend that they were misunderstood, and that other people were overreacting to a transient expression of hopelessness (McClay et al, 2018). In the authors' experience, given the circumstances of an assessment and the motivators for concealment, these statements are frequently deflections.…”
Section: Recommendation 4: Attend To Indications Of Minimization Of Suicidalitymentioning
confidence: 97%